Nitrogen Excretion and Aspects of Water Balance in Fasting Hooded Seal Pups (Cystophora cristata) - Coyle, Matthew (UiT Norges arktiske universitet, 2022)
The post-weaning fast of hooded seal pups (Cystophora cristata) is not well understood. What energy sources are being used? How is water balance maintained? How are these mechanisms balanced with thermoregulation? This study aims to answer some questions on the physiological mechanisms in place to assist an Arctic seal pup in the early stages of their life with no source of food or freshwater. Hooded Seals have some remarkable adaptations to birth on the ice; they have the shortest lactation period of any mammal at 3-5 days and therefore the pup is highly precocious. After weaning, the pups will fast for an estimated 30 days, relying on their energy sources built up during lactation until they are capable of foraging for themselves. Six pups were captured in the Greenland Sea at the end of, or shortly after, lactation. Measurements of metabolic rate and mass were made weekly alongside weekly sampling of blood and urine samples throughout their 30 days of post-weaning fast. Samples were then analysed for the concentrations of nitrogenous compounds and relevant ions (Cl- , Na+ , and Mg2+) to find how they may change over the month-long fasting period. From the analysis of nitrogenous products within the urine samples, the amount of protein catabolised over a 24- hour period was estimated, allowing for calculating the proportion of metabolic rate that is accounted for by the catabolism of proteins. Results here for electrolyte concentrations in plasma and urine support previous literature demonstrating that hooded seals are capable of ingesting seawater in order to maintain homeostasis. Urine osmolality increased to values higher than seawater (1.3±0.13 osmol/kg, compared with 0.949 osmol/kg in seawater), while haematocrit values stabilised after entrance to seawater. Weight-specific metabolic rates were not detected to significantly decrease over the fasting period (at an average of 2.4±0.54 W/kg, 1.7 times estimated Kleiber value) and the proportion of this that is accounted for by protein catabolism remained low ...